2005
DOI: 10.1002/rcm.2061
|View full text |Cite
|
Sign up to set email alerts
|

Tandem mass spectrometry of deprotonated iodothyronines

Abstract: In order to assist with the development of more selective and sensitive methods for thyroid hormone analysis the [M-H]-anions of the iodothyronines; T4, T3, rT3, (3,5)-T2 and the non-iodinated thyronine (T0) have been generated by negative ion electrospray mass spectrometry. Tandem mass spectra of these ions were recorded on a triple quadrupole mass spectrometer and show a strong analogy with the fragmentation pathways of the parent compound, tyrosine. All iodothyronines also show significant abundances of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…The CID spectrum of the precursor m / z 309.1 displays another interesting product at m / z 256.1 corresponding to the neutral OC 6 H 4 CH 2 loss from the tyrosine side‐chain. This loss, generally observed during the decomposition of deprotonated tyrosine‐containing peptides,40, 71–73 is thus another piece of information suggesting the deprotonation of the phenol group and, consequently, the zwitterionic form of the peptide (Scheme ). In competition with this direct cleavage, the formation of an ion–dipole complex, can also allow the OC 6 H 4 CH 2 to leave with a mobile proton from the carboxylic acid to generate a complementary pair of product ions, i.e.…”
Section: Resultsmentioning
confidence: 94%
“…The CID spectrum of the precursor m / z 309.1 displays another interesting product at m / z 256.1 corresponding to the neutral OC 6 H 4 CH 2 loss from the tyrosine side‐chain. This loss, generally observed during the decomposition of deprotonated tyrosine‐containing peptides,40, 71–73 is thus another piece of information suggesting the deprotonation of the phenol group and, consequently, the zwitterionic form of the peptide (Scheme ). In competition with this direct cleavage, the formation of an ion–dipole complex, can also allow the OC 6 H 4 CH 2 to leave with a mobile proton from the carboxylic acid to generate a complementary pair of product ions, i.e.…”
Section: Resultsmentioning
confidence: 94%
“…Further, it is also expected that the use of analyte/reference systems with similar metal ion affinity will allow the extension of the kinetic method for discriminating chemical and biologically isomeric compounds as well. The present study, based on the kinetic method, provides a useful addendum to the previously reported methods [37,38] in the analysis of thyroid hormone isomers in that the analysis of mixtures was facilitated with the help of metal-bound complex formation. Finally, the current experiments used for discrimination of isomers are not restricted to any particular metal ion for complex formation, generalizing the methodology, and thus confirm the readiness of the kinetic method for differentiation and quantification of other chemical compounds of pharmaceutical and biologic importance.…”
Section: Discussionmentioning
confidence: 94%
“…In this work, the relative molar percentages of T 3 and rT 3 isomers in a mixture were determined using a system of two equations. Couldwell et al [37] reported the fragmentation behavior of thyroid hormones T 4 , T 3 , rT 3 , [3,5]-T 2 , and the non-iodinated thyronine (T 0 ) in negative ion mode using ESI-MS/MS. In their work, the isomers, T 3 and rT 3 , are differentiated by observing the characteristic fragments at m/z values 359.7 and 604.5 for rT 3 , which are absent in the spectrum of T 3 .…”
mentioning
confidence: 99%
“…Figure A shows the EIC for this compound by monitoring the m / z ratio at 166.086 in the positive mode, corresponding to the peak eluted at 17.0 min; the MS/MS fragmentation of this precursor ion, [M + H] + produced two product ions, as shown in Fig. B; at m / z 120.0787 by cleavage of the COOH unit (45 Da) from the original L ‐phenylalanine structure that corresponds to the structure of the phenylethylamine molecule and the second product ion at m / z 103.0529 by subsequent loss of the ammonia unit (17 Da) …”
Section: Resultsmentioning
confidence: 99%